The virtual class and pedagogical interaction in the teaching and learning process for English B.A. Program, first-year students 2023, at Centro Regional Universitario de Veraguas - González Pimentel, Isaías
The current study examines the impact of the Virtual Class and Pedagogical Interaction on students enrolled in the English BA program at Centro Regional Universitario de Veraguas. The study's principal objective is to determine the relation The Virtual Class and Pedagogical Interaction in the Teaching and Leaming Process for English B.A. Program, first-year students 2023, at Centro Regional Universitario de Veraguas ship between Virtual Classes and Pedagogical Interaction in the English teaching and learning process. The study employed a quantitative approach with a correlational scope. The data was collected using a questionnaire, which was admimstered via Taily plafforms. The study included 45 students. The questionnaire comprised 20 questions on the variable of virtual class and pedagogical interaction, which were correlated with six dimensions that assess: direct response, indirect response, technological innovation, device, apps/platforms, and internet connection. The statistical software utilized for data analysis was Microsoft Excel and SPSS Statistics. The study reveals a correlation between students' perceptions of the impact of internet connection interruptions on pedagogical interaction. It reveals that although the current virtual class can substitute for in-person classes, numerous obstacles remain. However, this limitation does not dimimsh students' expectations for comprehensive virtual educational environments. Keywords: Virtual Class, Pedagogical Interaction, Teaching Process, Learning Process